Effect of deworming with Ivomec® on reproductive performance of yearling beef heifers - Robert L. Larson; L.R. Corah; M.F. Spire; R.C. Cochran (Kansas Agricultural Experiment Station Research Reports, 1992)
To determine the effect of deworming fallborn yearling heifers on reproductive parameters, 78 heifers were allotted to a either Ivomec® or control treatments. The heifers were dewormed in June and October when they were approximately 7 and 11 months old, respectively. Ivomec effectively lowered fecal egg counts from treated heifers compared to controls. In these heifers that were maintained on a marginal plane of nutrition, deworming not only improved weight gains but also hastened onset of puberty and improved conception rate during a 60-day breeding season. The positive effect of Ivomec on these reproductive characteristics could not be explained by increased weight gain alone, because the correlation between weight gain and puberty was not significant.
Keywords: Cattlemen& #x27; s Day; 1992; Kansas Agricultural Experiment Station contribution; no. 92-407-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 651; Beef; Beef heifers; Deworming; Puberty